The European Central Bank’s monetary pillar after the financial crisis - Dybowski, T. Philipp; Kempa, Bernd (Journal of Banking & Finance, 2020)
We apply a structural topic model (STM) to analyze European Central Bank (ECB) communication regarding the monetary pillar of its monetary policy strategy. We do so by quantifying the transcripts of the ECB President’s introductory statements at the press conferences that accompany the regular meetings of the ECB Governing Council. Our evidence shows that, within its monetary pillar, the ECB has gradually shifted its focus away from a genuine monetary analysis towards monitoring the stability of the European financial system. We go on to augment a standard Taylor rule by quantitative indicators obtained from the STM to assess whether the monetary pillar in general, and the shift in focus in particular, has had a measurable impact on the ECB’s monetary policy stance. We find that the monetary analysis has had a bearing on the interest rate setting in the early years of the ECB’s existence, but this influence completely disappears in the latter years of the sample. Furthermore, we find no evidence that financial stability considerations in the ECB communication have influenced interest rate decisions either before or after the financial crisis.